An Initial Exploratory Examination of the Sensitivity and Specificity of MyCog Mobile Using the Mini-Cog as a Proxy for Suspected Cognitive Impairment - Stephanie Ruth Young; Elizabeth Dworak; Greg Byrne; Yusuke Shono; Manrui Zhang; Julia Yoshino Benavente; Lihua Yao; Mike Bass; Laura Curtis; Maria Varela Diaz; Callie Jones; Richard Gershon; et al. (Journal of Primary Care & Community Health)
Objectives: To help promote early detection of cognitive impairment in primary care, MyCog Mobile was designed as a cognitive screener that can be self-administered remotely on a personal smartphone. We explore the potential utility of MyCog Mobile in primary care by comparing MyCog Mobile to a commonly used screener, Mini-Cog. Methods: A sample of 200 older adults 65+ years (mean age = 72.56 years), completed the Mini-Cog and MyCog Mobile, which includes 2 memory measures and 2 executive functioning measures. A logistic regression model was conducted to predict failing Mini-Cog scores (≤2) based on MyCog Mobile measures. Results: A total of 20 participants earned a Mini-Cog score ≤2. MyCog Mobile demonstrated an AUC of 0.83 (95% bootstrap CI [0.75, 0.95]), sensitivity of 0.76 (95% bootstrap CI [0.63, 0.97]), and specificity of .88 (95% bootstrap CI [0.63, 0.10]). The subtest Name Matching from MyFaces and MySorting were the only significant predictors of failed Mini-Cogs. Conclusions: MyCog Mobile demonstrated sensitivity and specificity to identify participants who failed the Mini-Cog, and may show promise as a screening tool for cognitive impairment in older adults. Further research is necessary to establish the clinical utility of MyCog Mobile in a larger sample using documented clinical diagnoses.